Curriculum Development Based on Local Cultural Wisdom at Al Jannah Early Childhood Education Unit Magelang Regency - Wiwiek Sumayni; Yuliantina, Irma (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to develop a curriculum for the Al Jannah Early Childhood Education (PAUD) unit that can optimize the integration of local cultural wisdom. This study uses the Four-D model where this model can be seen as a model for instructional development, namely: 1) Define; 2) Design; 3) Development; 4) Dissemination. The feasibility of the local cultural wisdom-based curriculum development product at the Al Jannah PAUD unit has been tested through expert validation and teacher perception analysis. The validation results from material experts show an average feasibility percentage of 77.22% (category "Good"), with the curriculum objectives component getting the highest score (86%) and the content/material component getting the lowest score (70%). Meanwhile, validation from cultural experts shows a higher feasibility percentage of 85.88% (category "Very Good"), with the Local Language aspect getting a perfect score (100%), followed by Regional Stories and Legends and Celebrations of Local Holidays (93.33%). The results of the teacher perception and readiness questionnaire also showed a very positive response (86% - "Very Good" category), although there is a gap between positive perceptions and implementation readiness, especially in terms of the availability of resources and teaching materials (20% - "Poor" category). Overall, the developed curriculum has met the eligibility standards for implementation in the Al Jannah PAUD unit with several improvements in the content/materials and implementation support aspects.